LETRA DE MECA: JAWI SCRIPT IN THE TAGALOG REGION DURING THE 16TH CENTURY - Donoso, Isaac (Journal of Al-Tamaddun, 2019)
History of writing in the Philippines has traditionally affirmed the eventual disappearance of pre-Hispanic script in the archipelago after Christianization. This affirmation ignores the relevance of Islamization in Manila bay. Accordingly, Jawi script became the dominant writing system in the Malay world from the 15th century onwards affecting also Tagalog culture, as several data confirm. This paper explores the use of Jawi script for Tagalog language and the cultural changes introduced by the Spanish establishment in Manila.